2013
DOI: 10.1128/genomea.00727-13
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequence Analysis of Postpandemic Influenza A(H1N1)pdm09 Virus Isolates from India

Abstract: The pandemic influenza A(H1N1)pdm09 virus was first detected in India in May 2009 and continued to circulate in the postpandemic period. Whole-genome sequence analysis of postpandemic A(H1N1)pdm09 viruses showed the circulation of clade 6 and clade 7 viruses. The hemagglutinin (HA) gene showed increased diversity compared with that in the pandemic phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 3 publications
2
8
0
Order By: Relevance
“…A thorough in silico analysis revealed that all of the 11 mutations common to the 2015 Indian sequences studied here, have been reported in different strains of influenza A(H1N1)pdm09 virus isolated from various parts of the world in the past [8][9][10]. However, to date, no single strain was reported to possess all these 11 mutations together, except the Indian 2015 strains sequenced in this study.…”
Section: Figurementioning
confidence: 73%
“…A thorough in silico analysis revealed that all of the 11 mutations common to the 2015 Indian sequences studied here, have been reported in different strains of influenza A(H1N1)pdm09 virus isolated from various parts of the world in the past [8][9][10]. However, to date, no single strain was reported to possess all these 11 mutations together, except the Indian 2015 strains sequenced in this study.…”
Section: Figurementioning
confidence: 73%
“…This concern seems relevant because the viral strain utilized for vaccine development (the influenza A/California/7/2009 strain) does not carry the mutant form of the HA protein (5). …”
Section: Genome Announcementmentioning
confidence: 99%
“…The epidemiology of H1N1pdm09 virus in the United Kingdom during 2009-2011 was characterized by 3 distinct waves: first wave, April-August 2009; second wave, September 2009-April 2010; and third wave, August 2010-April 2011 (Sridhar et al, 2013). In the post pandemic period, the virus remained in circulation and showed unusually increased activity and severity in March and April, for three consecutive years, which is certainly unseasonal (Dakhave et al, 2013). Since November 2013, the Public Health Agency of Canada has received a number of reports of illness caused by the influenza A H1N1 flu virus among young and middle-aged adults (http://www.phac-aspc.gc.…”
Section: Introductionmentioning
confidence: 97%